2019
DOI: 10.1002/cncr.32371
|View full text |Cite
|
Sign up to set email alerts
|

Surgical excision, Mohs micrographic surgery, external‐beam radiotherapy, or brachytherapy for indolent skin cancer: An international meta‐analysis of 58 studies with 21,000 patients

Abstract: BACKGROUND:The objective of this study was to compare the cosmesis and recurrence rates of conventional excision (CE), Mohs micrographic surgery (MMS), external-beam radiation therapy (EBRT), or brachytherapy (BT), for basal cell carcinoma and squamous cell carcinoma of the skin. METHODS: Population, Intervention, Control, Outcome, Study Design (PICOS), Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), and Meta-Analyses of Observational Studies in Epidemiology (MOOSE) methods were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 94 publications
(342 reference statements)
0
11
1
2
Order By: Relevance
“…Patients with NMSC in areas, which are cosmetically sensitive, are not ideal candidates for resection, particularly in cases where an extensive surgical defect may result or if a complex reconstruction is required. Preservation of tissue may be more achievable by radiotherapy for these patients, leading to improved cosmetic outcomes without increasing the risk of local failure [ 39 , 40 ]. A large-scale systematic review and pooled analysis found no statistically significant difference between local recurrence rates of SCC of the skin after Mohs micrographic surgery, external beam radiotherapy, and brachytherapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with NMSC in areas, which are cosmetically sensitive, are not ideal candidates for resection, particularly in cases where an extensive surgical defect may result or if a complex reconstruction is required. Preservation of tissue may be more achievable by radiotherapy for these patients, leading to improved cosmetic outcomes without increasing the risk of local failure [ 39 , 40 ]. A large-scale systematic review and pooled analysis found no statistically significant difference between local recurrence rates of SCC of the skin after Mohs micrographic surgery, external beam radiotherapy, and brachytherapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…RT may be used in first line in patients unable to undergo surgical resection, such as cosmetic or frail patients, to avoid significantly disfiguring surgery or orbital exenteration or in patients too frail to undergo general anaesthesia. A recent meta-analysis involving 21,000 patients showed comparable, extremely low one-year recurrence rates for both surgery and RT: 0.8%, 0.2%, 2%, and 0% for surgical excision, MMS, external beam irradiation, and brachytherapy (BT), respectively, and excellent cosmesis [55]. Different RT techniques, such as external beam RT, BT or electronic low energy sources (ELS), and schedules (i.e., normal fractionation or hypofractionation) can be selected depending on the expertise of the hospital.…”
Section: Role Of Radiotherapymentioning
confidence: 99%
“…With regard to cosmetic outcomes, a meta-analysis of 58 studies and 21,000 patients reported both brachytherapy and MMS as having improved cosmesis over external beam radiation and standard excision; recurrence rates at one year were similar across the modalities [ 82 ]. Another RCT of facial BCCs treated surgically or with RT revealed superior cosmetic results as assessed by dermatologists and patients at 4-years post-treatment [ 83 ].…”
Section: Topical Intralesional and Field Treatmentsmentioning
confidence: 99%